2008
DOI: 10.1007/s10620-008-0421-9
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Studies in Acute-on-Chronic Liver Failure

Abstract: The systemic hemodynamics in patients with ACLF is similar to that in decompensated cirrhotics. The portal pressure in these patients is higher than that in the compensated cirrhotics, and in the subgroup with large varices, it becomes similar to that of decompensated cirrhotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 29 publications
(38 reference statements)
3
33
0
2
Order By: Relevance
“…Hyperdynamic circulation and portal hypertension characterize ACLF, partially because of circulating mediators. While patients with ACLF with small varices had HVPG values (13.2 (±5.5) mm Hg) comparable with those of compensated cirrhotic patients, those with large varices had HVPG values comparable with those of decompensated cirrhotic patients (18.2 (±6.5) mm Hg) [59]. The data clearly showed that patients with small varices and lower HVPG levels have a higher chance of recovery after the acute insult settles down.…”
Section: Hemodynamics In Aclfmentioning
confidence: 73%
“…Hyperdynamic circulation and portal hypertension characterize ACLF, partially because of circulating mediators. While patients with ACLF with small varices had HVPG values (13.2 (±5.5) mm Hg) comparable with those of compensated cirrhotic patients, those with large varices had HVPG values comparable with those of decompensated cirrhotic patients (18.2 (±6.5) mm Hg) [59]. The data clearly showed that patients with small varices and lower HVPG levels have a higher chance of recovery after the acute insult settles down.…”
Section: Hemodynamics In Aclfmentioning
confidence: 73%
“…In a study from Delhi in adult patients, the predictors of mortality were encephalopathy, hepatorenal syndrome, GI bleed, platelets, serum sodium, HBV DNA and hepatic venous pressure gradient (HVPG) on univariate analysis, whereas on multivariate analysis only encephalopathy, platelet and HVPG independently predicted mortality. Etiology made no difference in mortality [11].…”
Section: Discussionmentioning
confidence: 90%
“…Eventhough the systemic hemodynamic alterations in ACLF are similar to patients with decompensated cirrhotics [79], the pathogenesis of renal dysfunction in ACLF is quite different in these patients as a major role is played by SIRS and subsequent sepsis [80]. Hence, both the circulatory and immune dysfunction are responsible for renal injury in these patients.…”
Section: Renal Failurementioning
confidence: 99%